Brainport Eindhoven: born from crisis - 25 years as a Triple Helix Governed Ecosystem - Mark Bronneberg; Jos Pieterse; Ger Post (Journal of Innovation Management, 2023)
Various researchers have called for research into positive examples of successful triple helix governed ecosystems. Triple Helix collaborations are seen as the solution to tackle the current ‘wicked problems’ of society. Researchers are encouraged to enhance our understanding of governing inter-organizational collaborations (ecosystems) in the context of university-industry-government (Triple Helix) relations. In this paper we therefore describe a case study of the Brainport Eindhoven ecosystem in the Netherlands which embodies a triple helix organization and how the regional governmental structure (Brainport Foundation and Brainport Development) on the one hand stabilizes at a strategic level and on the other hand gives flexibility at the tactical and operational level. This leads to the transfer of knowledge and to innovation and change within the network. Using mixed methods of 1) analysis of (strategic) documents about the regional governance used and how the Brainport Eindhoven mission evolved through time; 2) semi-structured interviews with current and former Brainport Foundation board members and former Brainport Development managers; and 3) network participant observations; we reveal rich experiences from 25 years of Brainport Eindhoven. This research shows the historical overview of Brainport Eindhoven and how the triple helix parties together managed several  regional or worldwide crises. This togetherness was crucial in the development of a successful regional ecosystem. Our findings illustrate the fragile balance between stability and flexibility within the ecosystem and its governance based on processes of common sensemaking by all stakeholders. Our paper contributes to a better understanding of the development and governance of triple helix entrepreneurial ecosystems. Finally, this paper makes suggestions for future research by discussing the ambition to transform the ecosystem into a Quadruple Helix (adding the ‘community’ as a fourth pillar) organized ecosystem.